Síntese, caracterização estrutural e avaliação do potencial antibacteriano e antioxidade de derivados do Eugenol e processos biocatalíticos usando casca da laranja. - Silva, Francisco Felipe Maia da (2017)
The use of natural products as a therapeutic source still consists of the main means to obtain drugs that are used in the fight against various diseases that affect man and other living things. Eugenol is a natural substance that has aroused the interest of several researchers in the world to present a diversity of biological properties, including: Antioxidant, antimicrobial, anesthetic, analgesic, hepatoprotective, anticoagulant among others. With this, the present work aimed at the synthesis of eugenol derivatives with subsequent analysis of its antioxidant and antibacterial activities. A study was also carried out aiming at increasing the number of derivatives produced by applying enzymes present in the orange peel (Citrus Sinensis), immobilized in a calcium alginate matrix as a biocatalyst in hydrolysis and esterification reactions. The work resulted in the synthesis, characterization and purification of twenty-one eugenol derivatives, characterized using hydrogen and carbon nuclear magnetic resonance spectroscopy, gas chromatography coupled to mass spectrometry and flame ionization detector, as well as high performance liquid chromatography. In the antibacterial activity it was observed that ten [4-allyl-2-methoxyphenyl 4-bromobenzoate (8); 4-allyl-3-methoxyphenyl 4-nitrobenzoate (9); 4-allyl-2-methoxyphenyl cinnamate (10); 4-(2-hydroxypropyl) -2-methoxyphenyl (12); 1- (4-acetoxy-3-methoxyphenyl) propano-2-yl acetate (13); 3-(4-hydroxy-3-methoxyphenyl)propane-1,2-diol (14); 3-(4-acetoxy-3-methoxyphenyl) propane-1,2-diyl diacetate (15); 2-methoxy-4-(oxiran-2-ylmethyl) phenol (16); 2-methoxy-4-(oxiran-2-ylmethyl)-phenyl acetate (17); 4-((2,2-dimethyl-1,3-dioxolan-4-yl)methyl)-methoxyphenol (18)] of the twenty-one derivatives showed antimicrobial activity, including against strains that the eugenol molecule was inactive, thus amplifying the spectrum of antibacterial action, and the derivatives with lower Minimal Inhibitory Concentration (500 μg / mL) were substances 8 and 16. As for the antioxidant activity, it was observed that all derivatives that were produced from the acylation reaction of the phenolic hydroxy group resulted in substances with a much lower antioxidant action (IC50˃200μg / mL) than eugenol (IC50 4.38μg / mL ), demonstrating that the phenol group is fundamental for the molecule to have the capacity to capture free radicals. On the other hand, the modification of the double bond by addition reaction in the alug group of eugenol, although slightly reducing the antioxidant capacity of the same (IC50 4.38 μg / mL for IC50 20 μg/mL in the hydration product), the effect is much lower than that of the structural change of the hydroxyl group, showing that even though it exerts some importance factor in the radical inhibition capacity, the allyl group is not as decisive for this activity as the hydroxyl group. The enzymatic extract from the orange peels immobilized on calcium alginate support was active both in hydrolysis reactions and in acetylation reactions, presenting enantiomeric excesses (ee) above 98% and chemoselectivity to hydroxy groups belonging to the alcohol function in detriment of the phenol, as well as regioselectivity for hydrolysis of acetoxy groups, maintaining intact benzoate groups. Orange peel enzymes have also been shown to be effective in ester synthesis reactions derived from primary alcohols (benzyl acetate) and poorly effective against cyclic alcohols. It was also verified the ability of the biocatalyst to work at different temperatures (30, 35 and 40 °C), good condition of reuse of the biocatalyst, besides the possibility of storage of the same. Orange peel enzymes have also been shown to be effective in ester synthesis reactions derived from primary alcohols (benzyl acetate) and poorly effective against cyclic alcohols. It was also verified the ability of the biocatalyst to work at different temperatures (30, 35 and 40 ° C), good condition of reuse of the biocatalyst, besides the possibility of storage of the same.